Reliable Control Architecture with PLEXIL and ROS for Autonomous Wheeled Robots (2017)
Today’s autonomous robots are being used for complex tasks, including space exploration, military applications, and precision agriculture. As the complexity of control architectures increases, reliability of autonomous robots becomes more challenging to guarantee. This paper presents a hybrid control architecture, based on the Plan Execution Interchange Language ( PLEXIL ), for autonomy of wheeled robots running the Robot Operating System ( ROS ). PLEXIL is a synchronous reactive language developed by NASA for mission critical robotic systems, while ROS is one of the most popular frameworks for robotic middle-ware development. Given the safety-critical nature of spacecraft operations, PLEXIL operational semantics has been mathematically defined, and formal techniques and tools have been developed to automatically analyze plans written in this language. The hybrid control architecture proposed in this paper is showcased in a path tracking scenario using the Husky robot platform via a Gazebo simulation. Thanks to the architecture presented in this paper, all formal analysis techniques and tools currently available to PLEXIL are now available to build reliable plans for ROS -enabled wheeled robots.